ANALISIS KANDUNGAN ZAT PENGAWET NATRIUM BENZOAT PADA SIRUP KEMASAN BOTOL YANG DIPERDAGANGKAN DI MALL MANDONGA DAN HYPERMART LIPPO PLAZA KOTA KENDARI - Hesti, Hesti (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2016)
This study was aimed to determine the content of sodium benzoate in the bottled syrup traded in Mall Mandonga and Lippo Plaza Hypermart Kendari, and to compare them with the preserpative amount allowed by the Indonesian Ministry of Health as set by Permenkes No. 033 / Menkes / Per / XI / 2012. This study was conducted in October up to December 2015. The study used a descriptive method; and the sodium benzoate content of the samples was analyzed in the food technology laboratory. The highest content of the sodium benzoate of 5904 mg/kg was found in the bottled syrup (DHT brand) traded in Mall Mandonga, whereas the lowest content of 432 mg/kg was found in the Fress brand traded in Hypertmart Lippo Plaza. The use of sodium benzoate preservative in the bottled syrup traded in Mall Mandonga was exceeding the amount permitted by the Ministry of Health. Key words : Sodium Benzoate, Syrup, Mall Mandonga, Hypertmart Lippo Plaza.